PENGGUNAAN MEDIA PENGAJARAN IPS SEJARAH DALAM PROSES BELAJAR MENGAJAR DI SMPN 9 PADANG - Sofwan, Muhammad; Zafri, Zafri; Nazmi, Ranti (Pendidikan Sejarah, 2013)
ABSTRACTThis study aims to describe how social studies teachers in the use of instructional media in SMPN IPS 9 Padang. This study aims to determine the type of tool used by teachers in the teaching and learning of history in the SMPN IPS 9 Padang and whether the media are used in accordance with the material presented. Ideally media that can be used in teaching and learning history is a map, images/photographs and documentary films. This research is a qualitative descriptive study with research sites in SMPN 9 Padang. The informants in this study include social studies teachers, amounting to 3 people, the principal and several students through observation, interview and document through the RPP. The accuracy of the materials research was tested by using triangulation, the materials research were analyzed with an interactive model that consists of data collection, data reduction , data display and conclusion. The results showed that the use of tool in teaching social studies in the history of the SMPN 9 Padang generally not been implemented to the fullest, because of the lack of tool  provided by the school. While factors - factors that cause teachers not using media in teaching social studies in the SMPN 9 Padang, among others: the lack of tool provided, even though the teacher is equipped with sufficient material and mature science in college, it can not guarantee that teachers can deliver material with more extensive and complete. Limitations of the media provided by the school teachers also resulted in less use of media in accordance with the material presented. From the above it can be concluded that the use of instructional media in SMPN 9 Padang IPS is not maximized because the teachers do not understand the function of the media and the lack of media in schools.  Key Words: Media, Teaching and Learning